Sorption of tetracycline antibiotics on natural and modified zeolite - Şalcıoğlu, Aslı Şükriye. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2007., 2007)
Antibiotics found in different compartments of environment are classified as emerging pollutants. Animal farming and aquaculture facilities are two potential sources for antibiotic pollution in the environment. In this study, the adsorption of widely used antibiotic, oxytetracycline (OTC) onto sodium (Na) and hexadecyltrimethylammonium (HDTMA) modified zeolite was investigated. The adsorption isotherm data were fitted to the Freundlich model. HDTMA-modified zeolite exhibited stronger pH dependence and 90 per cent antibiotic removal was achieved at pH 8 with 30 mg/L OTC. The adsorption capacity of Na-zeolite did not change significantly in the pH range of 2-10 and it exhibited a maximum OTC adsorption of 88 per cent at pH 6.5. The effect of various ions on the adsorption of OTC onto zeolite was also investigated. While the presence of calcium, magnesium, phosphate, chloride, and sulfate ions decreased the sorption of OTC onto Na and HDTMA-modified zeolite, bicarbonate ion promoted the adsorption of OTC on HDTMA-modified zeolite. NH4+ and OTC simultaneously removed from water by Na-zeolite. The obtained results show that both types of zeolites can be considered as a potential adsorbent for tetracycline antibiotics.|Keywords : Adsorption, zeolites, Oxytetracycline hydrochloride (OTC), UV spectroscopy, hexadecyltrimethylammonium (HDTMA)
Keywords: Adsorption.; Zeolites.; Oxytetracycline.; Ultraviolet spectroscopy.